ALOKASI WAKTU KERJA TENAGA KELUARGA PENYADAP KARET DI PTPN IX (PERSERO) KABUPATEN SEMARANG JAWA TENGAH - ARUMSARI, VINI (Universitas Sebelas Maret, 2009)
The aims of this research were (1) to know the work time allocation of the tapper or rubber household at off-sub sector of plaintation and (2) to know the factors that influenced the work time allocation of the tapper of rubber household at off-sub sector of plaintation.